2022
DOI: 10.1155/2022/6799414
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Networks, Management Approaches, and Emerging Treatments of Nonalcoholic Fatty Liver Disease

Abstract: The pathogenesis of NAFLD is complex and diverse, involving multiple signaling pathways and cytokines from various organs. Hepatokines, stellakines, adipokines, and myokines secreted by hepatocytes, hepatic stellate cells, adipose tissue, and myocytes play an important role in the occurrence and development of nonalcoholic fatty liver disease (NAFLD). The nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) contributes to the progression of NAFLD by mediating liver inflammation, immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 199 publications
(231 reference statements)
0
1
0
Order By: Relevance
“…Many studies have demonstrated that cellular networks rather than a single cell type in the liver modulate MASH progression (4)(5)(6). Among liver cells, hepatic macrophages can orchestrate both the progression and restoration of MASH by cross-talk with surrounding cells, such as hepatocytes, hepatic stellate cells (HSCs), liver sinusoidal endothelial cells, and so forth (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that cellular networks rather than a single cell type in the liver modulate MASH progression (4)(5)(6). Among liver cells, hepatic macrophages can orchestrate both the progression and restoration of MASH by cross-talk with surrounding cells, such as hepatocytes, hepatic stellate cells (HSCs), liver sinusoidal endothelial cells, and so forth (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%